Efektivitas Penerapan Activity-Based Costing dalam Meningkatkan Profitabilitas Perusahaan - Kaligis, Yuliana Fena; Arisman, Anton (MDP Student Conference, 2024)
The purpose of this research is to determine and compare the effect of Activity-Based Costing on Profitability: Assess whether the use of the Activity-Based Costing method has a positive impact on increasing company profits at the Roemah Merdeka Restaurant in Palembang. The research location was carried out at the Roemah Merdeka Restaurant in Palembang. The research method used is the Quantitative Method. The results of this research are the F Test Calculation Results with a calculated F value of 34.481, so it can be stated that the activity based costing method has an effect on increasing profitability at Roemah Merdeka Palembang. The T Test results are 6.203, so it can be concluded that the abc method has a significant effect on Roemah restaurant business profits independent. The determination number or R Square is 0.554 or equal to 55.40%.